Optimalisasi Kompetensi Mahasiswa PPG Otomotif Melalui Pendalaman Teknologi Kendaraan Hybrid dan Teknik Perawatannya di Kota Blitar - Irawan, Dani; Suhartadi, Syarif; Thohir, M. Anas; Ronald, Ronald; Solikah, Mar Atin (Civiliza Publishing, 2024)
One of the factors that supports the quality of vocational high school graduates needed by industry is how broad the knowledge of the latest technology is mastered by a teacher. On the other hand, there is still a gap between the developing technology and the level of mastery possessed by teachers. The competency standards possessed by teachers should ideally continue to increase along with technological developments. One indicator is the ownership of a teacher competency certificate in the automotive expertise field at the vocational school level. Therefore, efforts need to be made to develop a teacher's abilities. The method used is through training and workshops. The results of this community service activity were that most participants showed a significant increase in their understanding and skills in hybrid control systems, including theoretical and applied aspects. Teachers who took part in the training are now better prepared to implement hybrid technology in the learning process, supporting the transfer of knowledge to students better and more effectively.